Microfluidic and Static Organotypic Culture Systems to Support Ex Vivo Spermatogenesis From Prepubertal Porcine Testicular Tissue: A Comparative Study - Kanbar, Marc; de Michele, Francesca; Poels, Jonathan; Van Loo, Stéphanie; Giudice, Maria Grazia; Gilet, Tristan; Wyns, Christine (Frontiers in Physiology, 2022)
Background: In vitro maturation of immature testicular tissue (ITT) cryopreserved for fertility preservation is a promising fertility restoration strategy. Organotypic tissue culture proved successful in mice, leading to live births. In larger mammals, including humans, efficiently reproducing spermatogenesis ex vivo remains challenging. With advances in biomaterials technology, culture systems are becoming more complex to better mimic in vivo conditions. Along with improving culture media components, optimizing physical culture conditions (e.g., tissue perfusion, oxygen diffusion) also needs to be considered. Recent studies in mice showed that by using silicone-based hybrid culture systems, the efficiency of spermatogenesis can be improved. Such systems have not been reported for ITT of large mammals. Methods: Four different organotypic tissue culture systems were compared: static i.e., polytetrafluoroethylene membrane inserts (OT), agarose gel (AG) and agarose gel with polydimethylsiloxane chamber (AGPC), and dynamic i.e., microfluidic (MF). OT served as control. Porcine ITT fragments were cultured over a 30-day period using a single culture medium. Analyses were performed at days (d) 0, 5, 10, 20 and 30. Seminiferous tubule (ST) integrity, diameters, and tissue core integrity were evaluated on histology. Immunohistochemistry was used to identify germ cells (PGP9.5, VASA, SYCP3, CREM), somatic cells (SOX9, INSL3) and proliferating cells (Ki67), and to assess oxidative stress (MDA) and apoptosis (C-Caspase3). Testosterone was measured in supernatants using ELISA. Results: ITT fragments survived and grew in all systems. ST diameters, and Sertoli cell (SOX9) numbers increased, meiotic (SYCP3) and post-meiotic (CREM) germ cells were generated, and testosterone was secreted. When compared to control (OT), significantly larger STs (d10 through d30), better tissue core integrity (d5 through d20), higher numbers of undifferentiated spermatogonia (d30), meiotic and post-meiotic germ cells (SYCP3: d20 and 30, CREM: d20) were observed in the AGPC system. Apoptosis, lipid peroxidation (MDA), ST integrity, proliferating germ cell (Ki67/VASA) numbers, Leydig cell (INSL3) numbers and testosterone levels were not significantly different between systems. Conclusions: Using a modified culture system (AGPC), germ cell survival and the efficiency of porcine germ cell differentiation were moderately improved ex vivo. We assume that further optimization can be obtained with concomitant modifications in culture media components.